Using the Legacy Effect to Improve Patient Outcomes - Vinall, Maria (MD Conference Express, 2014)
Among individuals with diabetes, early intensive glycemic control is associated with long-term benefits 10 or more years later (ie, the legacy effect) [Holman RR et al. N Engl J Med 2008]. This article discusses the clinical implications of the legacy effect and the lag time before additional antihyperglycemic agents are added.